The Mediating Role of Information Technology Investment in the Relationship between Financial Inclusion Indicators and Institutional Performance in Jordanian Commercial Banks (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to determine the impact of financial inclusion indicators (customer use of financial services, customer access to financial services, and quality of financial services provided) on institutional performance (financial performance, customer satisfaction, internal processes, and learning and growth) with investment in information technology acting as an intermediary. The study employed a descriptive-analytical approach, utilizing the Statistical Package for the Social Sciences (SPSS) and AMOS software. The study population comprised all branch managers of Jordanian commercial banks, including head offices, totaling 647, as per the Central Bank of Jordan's 2024 annual report. A random sample of 266, representative of the study population, was selected. The study concluded that financial inclusion indicators (in their various dimensions) do indeed impact institutional performance (in their various dimensions) within Jordanian commercial banks. The coefficient of determination (R² = 0.397) was found, indicating that approximately 39.7% of the changes in institutional performance can be explained by financial inclusion indicators. The correlation coefficient was also found to be significant. (63.0%) indicates a strong positive correlation between financial inclusion and institutional performance. The study found that the standard direct impact of IT investment on institutional performance was (0.304), and that financial inclusion indicators explained (21.6%) of the indirect impact on institutional performance through IT investment in Jordanian commercial banks. Therefore, a positive impact of the independent variable (financial inclusion indicators) on the dependent variable (institutional performance) is evident through the mediating variable (IT investment) in Jordanian commercial banks, with a total impact of (0.892) at a significance level of (α≤0.05). The study recommended enhancing financial inclusion by banks adopting innovative and accessible programs for customers, along with improving service quality to ensure increased customer use of financial services and greater customer satisfaction.
Keywords: Financial Inclusion; Institutional Performance; Information Technology; Jordanian Commercial Banks